Beethoven's Orchestral Music: An Owner's Manual - Hurwitz, David (Rowman & Littlefield Publishers, 2021)
Veteran music critic David Hurwitz provides an accessible, comprehensive, and fresh survey of Beethoven’s symphonies, overtures, concertos, theatrical music, his single ballet and other music for the dance, and several short pieces worth getting to know. Beethoven’s orchestral works include some of the most iconic and popular pieces of classical music ever written. This book offers chapters on Beethoven’s handling of the symphony orchestra and his contributions to its evolution, as well as his approach to musical form in creating large, multi-movement works. The musical descriptions provide helpful strategies for listening that invite both beginners and experienced enthusiasts to treat even the best known pieces as something fresh, new and relevant. In addition, Hurwitz provides extensive lists of recommended recordings of all of the music surveyed, highlighting the wide range of issues in Beethoven interpretation and performance, as well as the history of his music. He encourages readers to listen actively and critically, as they build their own Beethoven discographies according to their personal tastes and preferences. The book is accompanied by online audio tracks of Beethoven works selected by Hurwitz.